Translator’s Frequent Lexis Store and Dictionary Use as Factors in SLT Comprehension and Translation Speed – A Comparative Study of Professional, Paraprofessional and Novice Translators - Ronowicz, Eddie; Hehir, Joanna; Kaimi, Toshihiro; Kojima, Keiko; Lee, Deok-Shin (Meta, 2005)
AbstractThis article examines empirical evidence on the use of translational aids from TAP studies over the last two decades and describes a think aloud protocol (TAP) study designed to verify some of these claims. Following a description of methodology used, the results of the study are presented and discussed. Basing on experience gained from the study, a number of methodological issues are then discussed: the use of students as subjects in TAP studies, the use of postgraduate students as co-investigators, as well as advantages and shortcomings of TAP methodology.